The Implications of Unveiling Cultural Hegemony Portrayed in a Pre-Intermediate Textbook For EFL Learning and Teaching (2019)
Cultural hegemony is understood as the practice of promoting and imposing a culture. Usually the culture imposed is from a politically powerful nation over a subordinate one (Fairclough, 2003). We became interested in understanding the discourse found within EFL textbooks that could be promoting cultural hegemony. Using these textbooks could have profound implications on language learning and teaching. This is not just a matter of using American or British English in an EFL textbook; rather, it is necessary to understand the intentions of the authors of these books. It could be that the purpose is to promote one culture, possibly their own culture, as the best one or the one to follow.